Treatment of Large Keloids with Secondary-Intention Healing. (September 2013) - Young, Phillip; Fisher, Michelle; Segel, Jamie; Stucker, Fred; Becker, Adam; Chen, Achih
Introduction: The use of secondary-intention healing for the treatment of large keloids of the neck and chest is described. Materials and Methods: Three patients presenting for treatment of large keloids in an academic and private practice setting were treated by resection with the CO2 laser and healing by secondary intention. After epithelialization, Kenalog was injected at monthly intervals for a total of 6 injections. Photodocumentation was carried out after epithelialization, if any changes were noted, and at the end of injections to monitor any regrowth. If regrowth was noted after comparing photos with the patient's current status, steroids were resumed. Results: There were mild recurrences of the keloid after the procedure; however, the patients demonstrated a notable improvement from the preoperative state, and patient satisfaction was high. Conclusions: The use of secondary intension healing for large keloids in the neck and chest is a unique method in the armamentarium of treatments for a difficult problem.